Formulation of Peanut and Red Palm Oil Spread as a Source of Beta-Carotene for Pregnant Women - Arwa Gemala; M. Rizal Martua Damanik (Journal of Indonesia Applied Nutrition (JIAN), 2026)
Vitamin A deficiency in pregnant women can cause problems in fetal development. The use of red palm oil, which is high in beta-carotene, can be used as a way to overcome vitamin A deficiency. This study aims to formulate peanut and red palm oil-based spread as a healthy food source of beta-carotene. This study used a completely randomized design (CRD) with three treatment levels of regular palm oil and red palm oil, namely F0 (100:0), F1 (50:50), and F2 (25:75) with 2 replications and duplo. Based on the analysis of physical characteristics, organoleptic properties, and nutritional content, the selected formula was F1). The organoleptic test used college students and pregnant women as panelists. One serving (20 g) contains 97 kcal of energy; 4.9 g of protein; 4.4 g of fat; and 9.4 g of carbohydrates, which meets 19.0% of the energy, 32.5% of the protein; 26.3% of the fat; and 13.6% of the carbohydrate requirements for pregnant women. The beta-carotene content of the selected F1 formulation is 359.15 mg/100 g, which is equivalent to 14.9 times that of carrots and 78.9 times that of tomatoes. The selected peanut butter formula meets the nutritional claim of being a protein source and contains beta carotene higher than carrots.